Development of a PVS3 plant vitrification method for cryopreservation of yacon (Smallanthus sonchifolius) genetic resources - Hammond, Stacy Denise Hammond; Zamecnik, Jiri; Faltus, Milos; Panis, Bart; Viehmannová, Iva (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):297